Germany and the Mediterranean Crossings: Suppressing Past Traumas and Revisiting Present Ones in Burhan Qurbani’s Berlin Alexanderplatz - Štefanić Brown, Kristina (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2024)
In the most recent cinematic adaptation of Alfred Döblin’s literary masterpiece Berlin Alexanderplatz, Burhan Qurbani (2020) reimagines the figure of Franz Biberkopf as Francis, an African refugee who, after almost drowning at sea during his perilous voyage to Europe, is shown trying to rebuild his life in modern-day Berlin. While Döblin’s novel focuses predominantly on issues of class, Qurbani’s rendition centers on racial inequalities and Otherness. Upon his arrival in Germany, Francis does everything in his power “to be good” and succeed in the modern metropolis, yet he is set up to fail at every step. Francis’s failure is largely due to the suppressed trauma of losing a loved one at sea and to the symbiotic relationship that forms between him and Reinhold, a German criminal who uses and abuses Francis for his own libidinal investment. It is a relationship of peculiar dependency that also embodies Germany’s dependency on migrants and evokes Germany’s colonial past. By analyzing the effect that trauma has on the protagonist, this essay aims to show that while Germany may be geographically distant from the Mediterranean (and often disassociates its own politics from the migrant crisis in the region), it is nevertheless affected by and tangentially involved in the tragedy that continuously unfolds in the region. By alluding to the contemporary politics of disassociation, the film emblematically portrays and underscores the notion that the Mediterranean has been a focal point of development for cultures since the antiquity and to this day remains a palimpsest marked by the incessant movement of people reaching and shaping destinations far beyond the countries touched by Mare Nostrum.